Targeted mass spectrometry for plasma glycoprotein profiling in pre-eclampsia - Dahabiyeh, Lina (2016)
Pre-eclampsia is a common hypertensive disorder of pregnancy that substantially affects maternal and neonatal morbidity and mortality worldwide. Despite decades of research, the aetiology of the disease remains poorly understood, and the clinical management of it is hampered by the lack of reliable diagnostic tests and effective therapy. Several screening tests have been suggested for the prediction of preeclampsia; however, none possess the sufficient specificity and sensitivity. Moreover, multiple pathways are known to be involved in the pathogenesis of pre-eclampsia, so it is very unlikely that a single or a small group of biomarkers will accurately predict the disease. In this thesis, two separate targeted LC-MS/MS methods were developed and validated to quantify plasma glycoproteins in pre- eclampsia to increase the pool of preeclampsia biomarker candidates and explore new pathways associated with the disease. The first method was hypothesis-driven and aimed to quantify the oxidation level of the plasma glycoprotein angiotensinogen (AGT), which has been proposed to be involved in the increased blood pressure characteristic of pre-eclampsia. The second method was hypothesis-generating and aimed to detect glycoprotein fold changes between different disease conditions using a simple and cost-effective conventional LC-MS/MS workflow.